1988
DOI: 10.1111/j.1475-1313.1988.tb01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐day variations in oculomotor function: 1. Tonic accommodation and tonic vergence

Abstract: Time‐of‐day variations were studied both in tonic accomodation and in tonic vergence. Thirty‐six male volunteers were measured once in the morning and at one other time on the same day. The mean baseline value of tonic accomodation was 2.02 D. Time‐of‐day variations were found, with a late evening measure being + 0.6 D greater than the morning value. No independent time‐of‐day fluctuations were found in tonic vergence. Post‐hoc analysis, however, showed that tonic vergence tended to shift in the same direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…Previous studies have shown that accommodation experiences daily fluctuations. [19][20][21] Our results are in line with Park et al, 19 because both studies have observed changes in accommodative amplitude values throughout day. However, Park et al 19 found an accommodative amplitude peak for 20-year-old participants in the afternoon, and we obtained an accommodative amplitude peak in the morning.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that accommodation experiences daily fluctuations. [19][20][21] Our results are in line with Park et al, 19 because both studies have observed changes in accommodative amplitude values throughout day. However, Park et al 19 found an accommodative amplitude peak for 20-year-old participants in the afternoon, and we obtained an accommodative amplitude peak in the morning.…”
Section: Discussionsupporting
confidence: 92%
“…Only tonic accommodation in the absence of visual stimuli has shown diurnal variations when objectively measured with a refractometer. 20,21,29 Here, we observed that the magnitude of the accommodative response was higher in the morning, and it decreased throughout the day. This behavior was observed for all the tested distances, showing greater statistically accommodative differences from the morning to evening at the closest distance (morning to evening accommodative magnitude: 20 cm, 0.2 D; 40 cm, 0.12 D; far, 0.15 D).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A recent study of day length changes in tonic accommodation shows that the amount of accommodation decreases from the morning to the beginning of the evening and approaches the morning value near the evening, and subsequently, there is an increase in the late evening [12]. Also, the effect of lighting on phoria, tonic accommodation during the day, and the use of different tools in measuring phoria have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst differences in the mean value of pre-task DF have been demonstrated with respect to the form of optometer used, it is unclear whether these variations influence the post-task shift in DF recorded following a period of sustained fixation. A recent study by Amerson and Mershon (1988) used a laser optometer to measure variations in DF with time of day. They noted the observations of Post, Johnson and Owens (1985) and Bullimore, Gilmartin and Hogan (1986) but suggested that the instrument remained valid to assess changes in D F if not the absolute values of accommodation.…”
mentioning
confidence: 99%